Hubungan Pengetahuan dan Kepatuhan Menggosok Gigi dengan Timbulnya Karies Gigi - Kala’tiku, Samsinta; Baharuddin; Rante Musu, Margaretha; Disik, Betriani; Asriawal (Media Kesehatan Gigi : Politeknik Kesehatan Makassar, 2023)
Context It is impossible to separate dental and oral health from general health of the body. A person is regarded to be in good health not only by looking well but also by having healthy teeth and mouth. As per Norfai & Rahman's (2021) analysis of data from the World Health Organization (WHO, 2020). Dental caries affects 80–90% of children under the age of 18, or those between the ages of 6 and 12, in European, American, and Asian nations, including Indonesia. The purpose is to ascertain how students at UPT SDN 2 Rantetayo relate to one another in terms of knowledge and adherence to tooth brushing. In 2023, this study was conducted at UPT SDN 2 Rantetayo. This research strategy uses a cross-sectional, quantitative research design. A deliberate sample was conducted. Forty responders provided this sample. In August 2023, this research was carried out. The study's findings indicated that there was a correlation (p=0.03<α=0.05) between students at UPT SDN 2 Rantetayo's knowledge and adherence to cleaning their teeth. Out of the 40 respondents, 24 (60.0%) had good knowledge; of these 24, 12 (30.0%) had good knowledge and followed through on brushing their teeth, and the remaining 24 respondents had good knowledge but did not follow through on brushing their teeth. up to 12 (30.0%) participants. In the meanwhile, 5 (12.5%) and 11 (27.5%) of the respondents, respectively, did not comply with cleaning their teeth due to ignorance. There is a correlation between students at UPT SDN 2 Rantetayo's knowledge and adherence to cleaning their teeth, according to the research's findings and the conversation that followed. Recommendations for how the school should handle the administration of kids cleaning their teeth in class and oversee it.